In vitro evaluation of fungicides, botanicals and biocontrol Agents for management of sheath blight of small millets - Krishnaveni, V; Savita, E; Lal, H C; Kudada, N (Indian Journal of Plant Protection, 2021)
In this study, 12 isolates of Rhizoctonia solani Kuhn (Teleomorph: Thanatephorus cucumeris) were selected based on its growth rate (slow, medium and fast growing) and used for management studies. Sensitivity of fungicides against 12 isolates showed that at 0.1% conc. triazole fungicides (propiconazole, difenconazole and tebuconazole) completely inhibited the mycelial growth and sclerotial production. In further evaluation of triazole fungicides at 0.05% conc. propiconazole & tebuconazole showed significant inhibition in mycelial growth and sclerotia. Among the botanicals, clove extract of Allium sativum (Garlic) showed maximum mycelial growth inhibition (78.52%). Bulb extract of Allium cepa (Onion) and rhizome extract of Zingiber officinale (Ginger) effectively reduced the sclerotial production. Among bio-control agents, Trichoderma harzianum (T. harzianum-H) procured from Hyderabad showed maximum inhibition of mycelial growth (88.89%).